Pacemaker choice optimization based on expected pacing requirement. (19th May 2022) - Breeman, KTN; Dijkshoorn, LA; Wilde, AAM; Tjong, FVY; Knops, RE
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Bradyarrhythmias are adequately treated with pacemakers. Currently, different pacing modes (single- and dual-chamber, cardiac resynchronization therapy and physiologic pacing) and types (leadless, transvenous) are available. Expected pacing requirement is an important factor in determining optimal pacing mode and type. Purpose: To evaluate atrial (AP) and ventricular pacing percentages (VP) over time, stratified by pacemaker indication. Methods: All consecutive patients ≥18 years with a DDD(R) transvenous pacemaker and ≥1 year follow-up at a tertiary center between January 2008 and January 2020 were retrospectively included. Baseline characteristics and AP and VP at yearly follow-up visits were assessed. Results: 714 patients were included, of which 210 (29%) with incomplete AV block (AVB), 261 (37%) complete AVB, 243 (34%) sinus node disease (SND). Mean age at implant was 72±13, 68±16, 67±14 years (p=0.005). AP and VP over time is shown in Figure. For incomplete AVB, median AP increased from 3% (1-24%) to 21% (1-49%) and VP from 37% (7-93%) to 91% (16-100%); for complete AVB, median AP increased from 3% (1-17%) to 10% (2-30%) and VP remained stable (98% [13-100%] to 99% [62-100%]); for SND, median AP increased from 26% (5-63%) to 55% (8-90%) and VP remained stable (3% [1-13%] to 5% [1-31%]). Conclusion: These results confirm the pathophysiology of different pacemaker indications, resulting in clear differences in pacing requirement over time and expected battery longevity. These results can be used to help guide optimal pacing mode and suitability for leadless or physiologic pacing.